Diastolic Pulmonary Gradient as a Predictor of Right Ventricular Failure After Left Ventricular Assist Device Implantation. Issue 16 (20th August 2019) - Alnsasra, Hilmi; Asleh, Rabea; Schettle, Sarah D.; Pereira, Naveen L.; Frantz, Robert P.; Edwards, Brooks S.; Clavell, Alfredo L.; Maltais, Simon; Daly, Richard C.; Stulak, John M.; Rosenbaum, Andrew N.; Behfar, Atta; et al.
Abstract : Background: Diastolic pulmonary gradient (DPG) was proposed as a better marker of pulmonary vascular remodeling compared with pulmonary vascular resistance (PVR) and transpulmonary gradient (TPG). The prognostic significance of DPG in patients requiring a left ventricular assist device (LVAD) remains unclear. We sought to investigate whether pre‐LVAD DPG is a predictor of survival or right ventricular (RV) failure post‐LVAD. Methods and Results: We retrospectively reviewed 268 patients who underwent right heart catheterization before LVAD implantation from 2007 to 2017 and had pulmonary hypertension because of left heart disease. Patients were dichotomized using DPG ≥7 mm Hg, PVR ≥3 mm Hg, or TPG ≥12 mm Hg. The associations between these parameters and all‐cause mortality or RV failure post LVAD were assessed with Cox proportional hazards regression and Kaplan–Meier analyses. After a mean follow‐up time of 35 months, elevated DPG was associated with increased risk of RV failure (hazard ratio [HR]: 3.30; P =0.004, for DPG ≥7 versus DPG <7), whereas elevated PVR (HR 1.85, P =0.13 for PVR ≥3 versus PVR <3) or TPG (HR 1.47, P =0.35, for TPG ≥12 versus TPG <12) were not associated with the development of RV failure. Elevated DPG was not associated with mortality risk (HR 1.16, P =0.54, for DPG ≥7 versus DPG <7), whereas elevated PVR, but not TPG, was associated with higher mortality risk (HR 1.55; P =0.026, for PVR ≥3 versus PVR <3). Conclusions: Among patients with pulmonary hypertension because of left heart disease requiring LVAD support, elevated DPG was associated with RV failure but not survival, while elevated PVR predicted mortality post LVAD implantation.